Assessment of Knowledge and Attitudes of Expectant Mothers towards HIV Screening and Counselling at Jachie-Pramso in the Ashanti Region of Ghana - Christiana Asiedu1; Evans Opoku Agyemang2; Emmanuel Appiah Agyei2 (University of Cape Coast, 2019)
The prevention of mother to child transmission (PMTCT) of human immunodeficiency virus (HIV) is paramount in safeguarding the lives of unborn children and young babies. The study sought to examine the knowledge and attitudes of expectant mothers towards HIV screening and testing in the Jachie-Pramso Community of the Ashanti Region. Methods: The study adopted a descriptive survey approach as its research design. The population of the study comprised 158 expectant mothers who were registered and attended regular antenatal care sessions at the community hospital. The census approach to sampling was adopted for the study. A structured questionnaire was used as the tool for data collection. Chi-square and descriptive statistics were used to analyse the data. Results: The findings from the study indicated that awareness level of HIV and its related issues were high among expectant mothers. It was also found that attitude of healthcare workers, community members and sexual partners are the main factors that prevent expectant mothers from patronising voluntary counselling and testing (VCT) services. It was generally, recommended that intensive educational programmes be instituted to sensitize both healthcare workers and the general public on discriminative behaviours. Conclusion: Most of the expectant mothers have knowledge of HIV and attitudes of the expectant mothers towards VCT of HIV were positive. The healthcare facility and its professionals may consider training the expectant mothers so they can act as snow-ballers in the dissemination of relevant health education and coerce other expectant mothers in the community to participate in the VCT and HIV programmes.
Keywords: Acquired Immune Deficiency Syndrome; Expectant Mothers; Human Immunodeficiency Virus; Voluntary Counselling and Test